Beyond English centrality: integrating expansive conceptions of language for literacy programming into IEPs - Ferrell, Amy L.; Soltero-González, Lucinda; Kamioka, Sakura (Frontiers in Education, 2024)
This article addresses the English centrality in reading policy, assessment, and instructional practices in the U.S. and its implications for the educational programing for emerging bilingual students (EBs) with disabilities. A recent review of the state of practice as it relates to EBs with disabilities reveals concerns that have endured for nearly six decades: biased assessment, disproportionality issues in special education, and teachers’ lack of understanding of language acquisition and students’ potential. These concerns demonstrate a need for the field to prioritize multilingual lenses for both the identification of and programming for EBs with disabilities. We propose attention to conceptions of language that expand beyond the structuralist standpoint that prevails in the current science of reading reform. We offer guiding principles for IEP development grounded in sociocultural perspectives when designing bilingual instructional practices, which can be applied to the educational programming for EBs with disabilities. Within a sociocultural view of bilingualism and biliteracy, language, and literacy are understood by multiplicities in use, practice, form, and function, in which all communicators draw from expansive meaning-making repertoires, whether in listening, speaking, reading, writing, viewing, and multimodally representing. By expanding conceptions of a student’s linguistic repertoire, we honor their use of language as one, holistic system in which their named languages plus a multitude of linguistic practices intersect and interact.